Analisis Keterampilan Kader Tentang Pemantauan Status Gizi Balita Usia 3 - 5 Tahun Dengan Metode Pemanfaatan Buku KIA Di Kelurahan Nagasari - Hodijah; Galaupa, Resi (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: The development of the health sector in Indonesia is directed at expanding the reach and improving the quality of basic health services, especially for mothers and children. One form of activity to expand the reach and improve the quality of health services is posyandu. Using the KIA Book is a strategy to empower the community, especially families, to maintain their health and receive quality maternal and child health services. Methods: This type of research uses analytical research methods with a cross sectional design. The population in this study was 35 cadres. The research sampling technique used accidental sampling. The sample in this research was 35 cadres. The analysis used in this research is the chisquare test. Results: Most of the respondents who had good skills were aged > 35 years as many as 8 people (53.3%) and aged 20-35 years as many as 7 people (46.7%). Most of the respondents who had good skills had a junior high school education of 8 people (53.3%), a high school education of 5 people (33.3%) and an elementary school education of 2 people (13.3%). Conclusion: There is a relationship between cadre skills regarding monitoring the nutritional status of toddlers aged 3 - 5 years with the method of using KIA books in Nagasari Village in 2023.